2014
DOI: 10.3389/fmolb.2014.00016
|View full text |Cite
|
Sign up to set email alerts
|

Standing of nucleic acid testing strategies in veterinary diagnosis laboratories to uncover Mycobacterium tuberculosis complex members

Abstract: Nucleic acid testing (NAT) designate any molecular approach used for the detection, identification, and characterization of pathogenic microorganisms, enabling the rapid, specific, and sensitive diagnostic of infectious diseases, such as tuberculosis. These assays have been widely used since the 90s of the last century in human clinical laboratories and, subsequently, also in veterinary diagnostics. Most NAT strategies are based in the polymerase chain reaction (PCR) and its several enhancements and variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 140 publications
(217 reference statements)
0
20
0
Order By: Relevance
“…In those studies, major discrepancies were reported for sensitivity (63 -97%) and speci city (50 -97%) values between PCRs for tissue samples with visible and non-visible lesions (13). After the introduction of Real-Time quantitative PCR (RT-qPCR) for the detection of MTBC members, sensitivity (74 -100%) and speci city (97 -100%) values were considerably increased, respectively compared to conventional PCR (13). Observed variability between studies did not only depend on the type of PCR (conventional, nested or RT-qPCR), but also on the number of PCR targets (single-or multiple copy) and reagents, the type and number of samples included, and the DNA isolation methods.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…In those studies, major discrepancies were reported for sensitivity (63 -97%) and speci city (50 -97%) values between PCRs for tissue samples with visible and non-visible lesions (13). After the introduction of Real-Time quantitative PCR (RT-qPCR) for the detection of MTBC members, sensitivity (74 -100%) and speci city (97 -100%) values were considerably increased, respectively compared to conventional PCR (13). Observed variability between studies did not only depend on the type of PCR (conventional, nested or RT-qPCR), but also on the number of PCR targets (single-or multiple copy) and reagents, the type and number of samples included, and the DNA isolation methods.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, antemortem TB diagnosis in these species still relies on mycobacterial culture of respiratory tract samples such as bronchoalveolar lavage uid (BALF) from rhinoceros or BALF and trunk washes (TW) from African elephants. Because mycobacterial culture is regarded as an imperfect gold standard (11,12), detection of mycobacterial DNA in animal samples has been used as an alternative or ancillary diagnostic method (12,13). In humans, PCR assays have become a common molecular tool for rapid detection of TB patients, and now can provide a de nitive diagnosis (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations